The occupational physical condition and muscle balance of air force pilots - Hannola, H.; Pahtaja, V.; Nieni, K.; Rintala, H. (International Journal of Computer Science in Sport, 2002)
Work-related musculoskeletal disorders (WMSDs) of Air Force pilots focus mainly on the skeletal framework. Under certain conditions, WMSDs of the cervical spine can develop into an officially classified occupational illness. Pilots who are in good physical shape also encounter these problems.Thus, it is presumed that factors other than those linked to purely physical performance may have some connection with the onset of WMSDs. In this study, we examine the connections between muscle balance and fitness characteristics as well as consider the significance of mobility in preventing disorders experienced by pilots.